Impact of Institutions on Schools, Teachers Work, and Marketing Related to Students Success in North Sumatra Province - Najiris Saleh Siregar; toyib daulay (International Journal of Society and Law, 2024)
The study aims to determine and test the effect of: (1) principal leadership affects teacher performance; (2) Does principal leadership affect school infrastructure; (3) Does principal leadership affect student learning achievement; (4) Does teacher performance affect student learning achievement; and (5) Does infrastructure affect student learning achievement. The study population was students at SMA Negeri 1 Sunggal, North Sumatra Province with a sample of 235 students. The research method is quantitative method with Smart-PLS analysis. The results of the study concluded: (1) principal leadership has an influence on teacher performance by 51.8%; (2) principal leadership has an influence on school infrastructure by 47.8%; (3) principal leadership has an influence on student learning achievement by 22.4%; (4) teacher performance has an influence on student learning achievement by 24.7%; and (5) school infrastructure has an influence on student learning achievement by 47.5%. Overall, the results showed that student learning achievement was influenced by principal leadership moderated by teacher performance and school infrastructure facilities by 53.4%; while the remaining 46.6% was determined by other factors.